Engineering a multifunctional chopper: enhancing livestock grass preparation - Dhani, Harsa (Mechanical, Energy and Material (METAL), 2025)
Indonesia is one of the countries that has great potential in the field of animal husbandry, currently farmers in Indonesia still use traditional methods to produce animal feed such as human-powered grass chopping which often faces obstacles in the form of limited labor, low time efficiency, and high operational costs. therefore, new technology is needed that can help farmers overcome these problems. The planning of a livestock grass chopping machine is driven by the need for increased efficiency and productivity in the livestock sector. This grass chopping machine is expected to be able to chop grass efficiently and effectively, produce quality animal feed and reduce the time and workload of farmers. there are several main parts in making a grass chopping machine, namely the frame, the engine drive motor dynamo, the cutting blade, the pulley, the V-belt and the casing. on this machine, 5 grasses are needed for one chopping which requires 1424.13 watts or 1.423 Kw of engine power, with a shaft diameter of 15.82 mm, a pulley diameter for the chopping shaft of 200 mm and a v-belt length of 54.396 in. The casing material used in this planning is aluminum alloy. While the cutting blade material is stainless steel.